What problems and challenges bring the pandemia at Public education in Lima Metropolitan? - Rojas Flores, Segundo Santiago (2023)
This article have the purpose of analyze the effects of Covid-19 in the public education in Lima Metropolitan. First, a general overview of the effects of the pandemia in different educational stakeholders and the differents challenges that they have taken up. From 9 interviews made principals, vice-principals, and teachers of the capital of the country, is possible to conclude that the connectivity problems coupled with a lack of adequate equipment for virtual clases, has increased inequality in access to education at all educational levels. Further, we have to highlight the psychological effects of the pandemic, essentially with emotional problems in the persons involved.